Half a World : Regional Inequality in Five Great Federations - Milanovic, Branko (World Bank, Washington, DC, 2012)
The paper studies regional (spatial) inequality in the five most populous countries in the world: China, India, the United States, Indonesia, and Brazil in the period 1980-2000. They are all federations or quasi-federations composed of entities with substantial economic autonomy. Two types of regional inequalities are considered: Concept 1 inequality, which is inequality between mean incomes (GDP per capita) of states/provinces, and Concept 2 inequality, which is inequality between population-weighted regional mean incomes. The first inequality speaks to the issue of regional convergence, the second, to the issue of overall inequality as perceived by citizens within a nation. All three Asian countries show rising inequality in terms of both concepts in the 1990s. Divergence in income outcomes is particularly noticeable for the most populous states/provinces in China and India. The United States, where regional inequality is the least, shows further convergence. Brazil, with the highest level of regional inequality, displays no trend. A regression analysis fails to establish robust association between the usual macroeconomic variables and the two types of regional inequality.